Analisis Estimasi dan Faktor-faktor yang Memengaruhi Tingkat Profitabilitas Bank Umum Syariah di Indonesia (Studi Kasus PT Bank Syariah Mandiri Periode 2008-2011) - Rizkita Alhamditia, Era; Heykal, Mohamad (Binus Business Review, 2013)
The purpose of this study is to determine which among the model Return on Assets, Return on Equity, and Gross Profit Margin is best used as a model for estimation of profitability of Bank Syariah Mandiri and to determine whether the level of funding for the results, capital, operating efficiency, and liquidity influential together (simultaneously) or partially on the level of profitability of Bank Syariah Mandiri using multiple linear regression. The method used in this research is quantitative method using secondary data monthly financial statements of Bank Syariah Mandiri from period 2008-2011. The dependent variable in this study is the ROA, ROE, and GPM. Meanwhile, the independent variable is the MMR, CAR, ROA, and FDR. Results from this study are the ROA model is the best estimate that can be used to measure the profitability of Bank Syariah Mandiri seen from the influential of three independent variables that significantly effect on the ROA model. Then, the level of mudharabah financing for the results (MMR) is significant negative effect on profitability in the model of ROE, while the model is not significant for ROA and GPM. The CAR has significant negative effect on ROA and ROE models, but has no significant effect on the model GPM. BOPO is significant negative effect on ROA and GPM models, but is no significant effect on ROE. FDR is significant negative effect only on the ROA, and is not significant on the ROA and GPM model.